(untitled) (Research, Society and Development, 2020)
Cerrado has a diverse flora that occurs in different physiognomies. One of the striking features of the biome is the occurrence of well-defined rainy and dry seasons. During drought, Cerrado plants are subject to water restrictions. Stomata, which are epidermal structures responsible for gas exchanges, are essential for maintaining the plant water status. Ichthyothere terminalis (Spreng.) Blake is an herbaceous Asteraceae widespread e in the open Cerrado physiognomies. The species has a thickened underground system, which contributes to the plant’s persistence in the environment. At the end of the drought, the aerial organs resprout. The objective of this work was to evaluate the stomatal dimensions in leaves of Ichthyothere terminalis at different seasons. Collections were carried out in open Cerrado physiognomies in dry and rainy periods, in which the plants were in different phenological phases. The leaves were collected, preserved, and fixed following the usual methods for anatomical and histometric analysis. The epidermis was cleared, and measurements and counts were made under a light microscope. The leaves of Ichthyothere terminalis are amphistomatic, with higher stomatal density on the abaxial surface. The density of stomata on the abaxial surface was higher in the transition between dry and rainy seasons. The area of the stomatal pores was greater at the beginning of the drought on both epidermal surfaces. The species showed the ability to change the attributes of stomata in different seasons, and this can contribute to its occurrence in habitats subject to seasonal drought.